Age-dependent effects of cord blood long-chain PUFA composition on BMI during the first 10 years of life. Issue 11 (14th June 2014) - Standl, Marie; Thiering, Elisabeth; Demmelmair, Hans; Koletzko, Berthold; Heinrich, Joachim
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, we investigated whether n-6 and n-3 long-chain PUFA (LC-PUFA) concentrations in cord blood (CB) serum are associated with BMI up to 10 years of age, after accounting for LC-PUFA composition at 2, 6 and 10 years. The study was based on 388 participants of the German LISAplus (Influence of Lifestyle-Related Factors on the Immune System and the Development of Allergies in Childhood Plus the Influence of Traffic Emissions and Genetics) birth cohort study carried out in Munich. BMI was measured at 2, 6 and 10 years of age. Serum phospholipid fatty acid concentrations were measured by GC in CB and in blood collected at 2, 6 and 10 years of age. The association between n-3 LC-PUFA and n-6 LC-PUFA concentrations and n-6:n-3 LC-PUFA ratio in CB serum glycerophospholipids and BMI z-scores was assessed using linear mixed models adjusted for LC-PUFA composition at follow-up and potential confounders. Interaction terms between time of follow-up and LC-PUFA concentrations in CB were included. There was no consistent association between n-6 and n-3 LC-PUFA concentrations in CB and BMI over time. However, there was a significant interaction between n-6:n-3 LC-PUFA ratio in CB and time of follow-up with respect to BMI (P= 0·0415): a negative effect at 2 years; no effect at 6 years; a positive effect at 10 years. BMI up to 10 years of age may be influenced by the n-6:n-3 ratio in CB serum glycerophospholipids in a time-varying fashion. The present results thereby highlight the importance of considering age when examining associations between fatty acid concentrations and BMI.